2019
DOI: 10.3389/fpsyt.2019.00103
|View full text |Cite
|
Sign up to set email alerts
|

Statins and Inflammation: New Therapeutic Opportunities in Psychiatry

Abstract: Statins, which are widely used to treat hypercholesterolemia, have anti-inflammatory and anti-oxidant effects. These are thought to be responsible for the potential effects of statins on various psychiatric disorders. In this study, we comprehensively review the literature to investigate the effects of statins on various psychiatric disorders including depression, schizophrenia, and dementia. In addition, we review adverse effects and drug interactions of statins to give clinically useful information guiding s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 180 publications
(184 reference statements)
4
76
0
Order By: Relevance
“…Abbreviations: ADHD, attention deficit and hyperactivity disorder; miRNA, micro RNAs; NAFLD, non-alcoholic fatty liver disease; OH, alcohol; PNPL A3, patatin-like phospholipase domain-containing protein 3; PTSD, post-traumatic stress disorder diminishing free cholesterol and have been found to protect against histological damage [107]. As they have antiinflammatory and anti-oxidative effects, they have also been proposed as adjuvant therapies for a number of psychiatric disorders [108]. Another interesting example of common pathways and treatment can be found in the role of cannabinoid 1 receptor, which modulates the hepatic energy state and food intake, and could play a role in the development of hepatic steatosis [109].…”
Section: Treatmentmentioning
confidence: 99%
“…Abbreviations: ADHD, attention deficit and hyperactivity disorder; miRNA, micro RNAs; NAFLD, non-alcoholic fatty liver disease; OH, alcohol; PNPL A3, patatin-like phospholipase domain-containing protein 3; PTSD, post-traumatic stress disorder diminishing free cholesterol and have been found to protect against histological damage [107]. As they have antiinflammatory and anti-oxidative effects, they have also been proposed as adjuvant therapies for a number of psychiatric disorders [108]. Another interesting example of common pathways and treatment can be found in the role of cannabinoid 1 receptor, which modulates the hepatic energy state and food intake, and could play a role in the development of hepatic steatosis [109].…”
Section: Treatmentmentioning
confidence: 99%
“…Statins reduce inflammatory biomarkers and inhibit the activation of inflammatory transcription, leading to neuroprotection. Simvastatin has been linked to altered cytokine secretion (IL-1β and TNF-α) and upregulated endothelial NOS (eNOS) [119]. In addition, statins are thought to exhibit antioxidant effects via ROS production inhibition and have beneficial effects on endothelial function, coronary and cerebral blood flow and haemostasis [120,121].…”
Section: Statinsmentioning
confidence: 99%
“…Atorvastatin has been found to promote angiogenesis and enhance functional recovery after stroke by promoting cerebral blood flow [122]. Pre-treatment with rosuvastatin has similar outcomes to minocycline, in terms of improved neurological score and reduced infarct volume [119]. A prospective, non-randomised patient study found that rosuvastatin treatment improved NIHSS scores (OR of 0.04 for NIHSS score of 15 (95% CI, 0.003 to 0.93)) and reduced mortality (OR of 0.20 (95% CI, 0.02 to 1.67)) in intracerebral haemorrhage (ICH) [123].…”
Section: Statinsmentioning
confidence: 99%
“…There is also support for the view that the statin treatment decreases both: inflammation and cholesterol levels. Recently, [ 39 41 ] have found that the use of statins as the anti-inflammatory, anti-oxidant, and immuno-modulatory drugs, in addition to their known lipid-lowering effect, proved to be beneficial in the context of many diseases. In particular, these authors assert that statins exert a direct anti-atherosclerotic effect on the arterial wall, beyond their effects on plasma lipids.…”
Section: The Essence Of Atherogenesismentioning
confidence: 99%